Life expectancy of HIV-positive individuals on combination antiretroviral therapy in Canada - Patterson, Sophie; Cescon, Angela; Samji, Hasina; Chan, Keith; Zhang, Wendy; Raboud, Janet; Burchell, Ann N; Cooper, Curtis; Klein, Marina B; Rourke, Sean B; Loutfy, Mona R; Machouf, Nima; et al. (Université d'Ottawa | University of Ottawa, 2015)
Abstract Background We sought to evaluate life expectancy and mortality of HIV-positive individuals initiating combination antiretroviral therapy (ART) across Canada, and to consider the potential error introduced by participant loss to follow-up (LTFU). Methods Our study used data from the Canadian Observational Cohort (CANOC) collaboration, including HIV-positive individuals aged ≥18 years who initiated ART on or after January 1, 2000. The CANOC collaboration collates data from eight sites in British Columbia, Ontario, and Quebec. We computed abridged life-tables and remaining life expectancies at age 20 and compared outcomes by calendar period and patient characteristics at treatment initiation. To correct for potential underreporting of mortality due to participant LTFU, we conservatively estimated 30 % mortality among participants lost to follow-up. Results 9997 individuals contributed 49,589 person-years and 830 deaths for a crude mortality rate of 16.7 [standard error (SE) 0.6] per 1000 person-years. When assigning death to 30 % of participants lost to follow-up, we estimated 1170 deaths and a mortality rate of 23.6 [SE 0.7] per 1000 person-years. The crude overall life expectancy at age 20 was 45.2 [SE 0.7] and 37.5 [SE 0.6] years after adjusting for LTFU. In the LTFU-adjusted analysis, lower life expectancy at age 20 was observed for women compared to men (32.4 [SE 1.1] vs. 39.2 [SE 0.7] years), for participants with injection drug use (IDU) history compared to those without IDU history (23.9 [SE 1.0] vs. 52.3 [SE 0.8] years), for participants reporting Aboriginal ancestry compared to those with no Aboriginal ancestry (17.7 [SE 1.5] vs. 51.2 [SE 1.0] years), and for participants with CD4 count <350 cells/μL compared to CD4 count ≥350 cells/μL at treatment initiation (36.3 [SE 0.7] vs. 43.5 [SE 1.3] years). Life expectancy at age 20 in the calendar period 2000–2003 was lower than in periods 2004–2007 and 2008–2012 in the LTFU-adjusted analyses (30.8 [SE 0.9] vs. 38.6 [SE 1.0] and 54.2 [SE 1.4]). Conclusions Life expectancy and mortality for HIV-positive individuals receiving ART differ by calendar period and patient characteristics at treatment initiation. Failure to consider LTFU may result in underestimation of mortality rates and overestimation of life expectancy.